PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN LEAFLET DAN PHANTOM TERHADAP KETERAMPILAN IBU MERAWAT BAYI - Ismiyanti Achmad (Poltekkes Kemenkes Maluku, 2021)
A mother is the primary caregiver for her baby. However, sometimes mothers feel less confident in caring for their babies. They need to be assisted with education about baby care to increase their confidence and be more skilled in caring for their babies. This study aims to determine the effect of health education using leaflet and phantom on the skills of mothers to care for babies. The method used is a quasi-experimental approach with a pretest-posttest control group design approach. The research was conducted in the postpartum room at RSUD dr. M. Haulussy with samples of primiparous mothers consisting of 30 intervention groups and 30 control groups determined by purposive sampling technique. Data were obtained through questionnaires and checklists and analyzed using the Wilcoxon, Man Whitney and Chi square tests. The results showed a change in the improvement of maternal skills after health education as much as 80% of mothers in the intervention group, while in the control group it was 50%. Health education during the taking hold period by using media/tools such as leaflets and phantoms was proven to have an effect on the mother's skills in caring for the baby.